2023
DOI: 10.3390/healthcare11182546
|View full text |Cite
|
Sign up to set email alerts
|

Integrative Korean Medicine Treatments for Traumatic Facial Palsy Following Mandibular Fracture: A Case Report and Literature Review

Hyunsuk Park,
Sook-Hyun Lee,
Yeonsun Lee
et al.

Abstract: Prior studies exploring the effectiveness of traditional Korean medicine (TKM) treatment for facial palsy have mainly focused on Bell’s palsy, and there are few studies on the effectiveness of TKM treatments for traumatic facial palsy following mandibular fracture. The patient was a 24-year-old Korean man with left-sided facial paralysis following a left mandibular fracture. Surgery was performed for the fracture and the facial palsy was treated using conventional medicine (CM) treatments for approximately 3 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Therefore, we emphasized the feasibility of implementing the COS in primary KM clinical settings. Drawing from previous studies in KM clinics ( 7 , 29 ), our goal was to develop a practical and effective COS with simple, accurate outcomes that seamlessly integrate into routine clinical practices without significant disruption. In developing the COS-FP-KM, we paid special attention to selecting outcomes that align with the practical realities of these clinical settings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, we emphasized the feasibility of implementing the COS in primary KM clinical settings. Drawing from previous studies in KM clinics ( 7 , 29 ), our goal was to develop a practical and effective COS with simple, accurate outcomes that seamlessly integrate into routine clinical practices without significant disruption. In developing the COS-FP-KM, we paid special attention to selecting outcomes that align with the practical realities of these clinical settings.…”
Section: Discussionmentioning
confidence: 99%
“…FP often manifests suddenly and significantly impacts patient quality of life by affecting facial expressions and functions (1)(2)(3)(4)(5). While treatments including corticosteroids, antiviral agents, and HM are typically effective within three weeks to three months (28,29), around 30% of patients may still suffer from enduring complications such as permanent facial weakness, even after undergoing proper treatment (30). During the consensus process, the PMG and experts agreed on the importance of considering a broad range of physical and psychological factors in the COS for FP.…”
Section: Discussionmentioning
confidence: 99%
“…In meditation, corticosteroids, drops, ointments, and botulinum toxin are known to be used to treat FNT [17,19]. Park et al (2023) [20] noted that acupuncture, pharmacopuncture, moxibustion, cupping, bloodletting, hyperbaric oxygen therapy, physiotherapy, TEA, and herbal medicine are used variably. In IKM, no study has reported PS-induced FNT cases; temporal fractures, zygomatic fractures, and skull fractures or head traumas are common [20].…”
Section: Jarmentioning
confidence: 99%
“…Park et al (2023) [20] noted that acupuncture, pharmacopuncture, moxibustion, cupping, bloodletting, hyperbaric oxygen therapy, physiotherapy, TEA, and herbal medicine are used variably. In IKM, no study has reported PS-induced FNT cases; temporal fractures, zygomatic fractures, and skull fractures or head traumas are common [20]. In a 2018 review article by Jeong et al [4], 37 cases of FP caused by FNT included otologic surgery and temporal fracture, whereas common treatments included acupuncture and Korean herbal medicine.…”
Section: Jarmentioning
confidence: 99%